KEBIJAKAN DINAS TRANSMIGRASI DAN TENAGA KERJA KABUPATEN SIAK DALAM PENEMPATAN TENAGA KERJA DAN PERLUASAN KERJA TAHUN 2017 - Ainil Mardiah; Erman M (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Employment is a condition in which a person is looking for a job or does not have a job while he is in the work force. This study aims to determine the policies of the Transmigration and Manpower Office of Siak Regency in the Implementation of Manpower Placement and Employment in 2017. The location of this research is at the Department of Transmigration and Manpower of Siak Regency. This research uses a qualitative approach. This type of research is descriptive. Data were collected through informants purposively. Data collection techniques using interviews, observation, and documentation.The results showed that the policies of the Department of Transmigration and Manpower of Siak Regency in the Implementation of Manpower Placement and Job Expansion in 2017 were divided into 2, namely, open unemployment and underemployment caused by lack of expertise, unsupportive regional conditions.Keywords: Manpower Placement, Job Expansion